Hubungan Perceived Stress dengan Sedentary Behavior pada Mahasiswa Universitas Negeri Padang - M.Farhan Kurniawan; Hanifa Laura Dalimunthe (TSAQOFAH, 2026)
Although sedentary behavior and psychological pressure are increasingly prevalent in university students’ lives, the relationship between perceived stress and sedentary behavior among students at Universitas Negeri Padang has not yet been extensively explained empirically. This study aimed to analyze the relationship between perceived stress and sedentary behavior among students at Universitas Negeri Padang. The study employed a quantitative approach with a non-experimental correlational design and involved 400 students selected through purposive sampling. Data were collected using the Perceived Stress Scale-10 (PSS-10) and the Modified Sedentary Behavior Questionnaire (MSBQ) and were subsequently analyzed using Spearman rank correlation. The findings showed that the majority of respondents had perceived stress in the moderate category (76.8%) and sedentary behavior in the moderate category (54.5%). The correlation test yielded a coefficient of 0.012 with a significance value of 0.816, indicating that there was no significant relationship between perceived stress and sedentary behavior. These findings indicate that the level of sedentary behavior among students was not significantly associated with perceived stress in this study and may be related to other factors, such as academic demands, digital device use, study habits, physical activity, and environmental conditions. This study provides an empirical basis for universities to develop stress management and sedentary behavior reduction programs as two separate but complementary interventions to support student well-being.